Experimental investigation of Jujube seed oil in VCR for different nozzles. (2020) - Mahesh, R.; Muthurajan, Dr.K.G.; Senthilkumar, A.
Highlights: The Research work which i had performed in four stroke single cylinder VCR engine using Jujube seed oil. The experiment was conducted by transesterification method. The emission characteristics of Nitric oxide and carbon dioxide found to be increasing. Abstract: The Petroleum resources are depleting rapidly. Biodiesel is one of the most favourable alternatives for Fossil Fuels. Vegetable oils are coming from agricultural sources. Hence CO2 emission in the environment can be reduced when compared to petroleum products. In this investigation Jujube Methyl Ester is prepared by transesterification method using Potassium hydroxide (KOH) as catalyst. It is used in Four Stroke, single cylinder variable comparison engine (VCR). The rated speed of the engine is 1500 rpm at different loads. The engine performance was analyzed for different nozzle and blends. Nitric oxide (NOx) and Particular matter (PM) are slightly increased. Carbon dioxide (CO2) is apparently increases with load whereas HC is found to be decreasing with load. Carbon monoxide (CO) emission is high for this.